2023
DOI: 10.3390/plants12030447
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Regulate Plant Secondary Metabolites

Abstract: Abiotic environmental stresses can alter plant metabolism, leading to inhibition or promotion of secondary metabolites. Although the crucial roles of these compounds in plant acclimation and defense are well known, their response to climate change is poorly understood. As the effects of climate change have been increasing, their regulatory aspects on plant secondary metabolism becomes increasingly important. Effects of individual climate change components, including high temperature, elevated carbon dioxide, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 198 publications
4
54
0
Order By: Relevance
“…Another insightful climatic index was ASR in durum wheat, which was positively correlated with four terpenes: α ‐thujene, cis ‐ β ‐farnesene, p ‐cymene, and the trans ‐calamenene mentioned above. These results were in accordance with those reported by several authors focusing on different plants and summarized in a recent review underlining the influence on secondary metabolites as response to high and low light intensity 36 …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Another insightful climatic index was ASR in durum wheat, which was positively correlated with four terpenes: α ‐thujene, cis ‐ β ‐farnesene, p ‐cymene, and the trans ‐calamenene mentioned above. These results were in accordance with those reported by several authors focusing on different plants and summarized in a recent review underlining the influence on secondary metabolites as response to high and low light intensity 36 …”
Section: Resultssupporting
confidence: 93%
“…Drought stress associated with long dry spells (CDD) strongly affected the common wheat VOC profile, followed by indices related to temperature. Other authors reported that phenolics and terpenoids exhibited high variability in response to drought and about the 60% of these terpenes increased in response to drought stress 36 . However, PLS‐R analysis calculated only one out five important terpenes increasing with CDD, suggesting a slightly divergent trend in comparison with the literature.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Intra-specific variation of chemical constituents could be found among populations, but it was a common phenomenon found generally in other researches ( Chen et al 2015;Saraf and Shinede 2016;Saraf and Shinede 2018) . Production and accumulation of phytochemicals are not only dependent on the plant species but also the environmental factors (Qaderi et al 2023), which were concerned in this study. The roots and stems were thus collected from the plants which were more or less the same age, same size and in the same rainy season.…”
Section: Discussionmentioning
confidence: 99%
“…These secondary metabolites also play significant roles in human society as valuable compounds for use in pharmaceuticals, cosmetics, and nutraceuticals. [25,26] As it is known, Fourier transform infrared spectroscopy (FTIR) is more sensitive, rapid, and environmentally friendly compared to other chemical methods. At the same time, it is a technique that not only provides qualitative and quantitative information about the chemical structure but also provides information about the molecular conformation and the interaction between neighboring molecules.…”
Section: Introductionmentioning
confidence: 99%